Surgical Site Infections by Mycobacterium after Cesarean Section in Bangladesh: A Case Report - Islam, M. Saiful; Yusuf, M. Abdullah; Ashraf, Fatema (Bangladesh Journal of Infectious Diseases, 2015)
Surgical site infection is very common in Bangladesh which is due to several reasons. During caesarean section it is not unlikely that this type of infection can be happened. In addition to the common bacteria atypical bacteria sometimes causes the surgical site infection like Mycobacterium species. In this case report a cesarean section-acquired Mycobacterium surgical site infections has been reported in Bangladesh which was presented as repeated abscess formation at the site of the caesarean section. Pus was drained from the abscess and Zeil-Neelsen staining was performed and was found slender rod, beaded appearance Acid-fast bacilli. Then the patient was treated with anti-tubercular drugs and was totally cured. Bangladesh J Infect Dis 2014;1(1):18-21<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />